ANALISIS KASUS HAM DI DUNIA (PEMBANTAIAN TERORISME DI MOZAMBIK) - Muhammad Syailendra Sulistyowati (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2024)
Militant attacks and operations by security forces in Mozambique's Cabo Delgado province has claimed nearly 3,000 lives, while hundreds of thousands of people evacuate. Insecurity has prompted the suspension of massive gas projects. Country Islam (ISIS) claims ties to the insurgency. The South African government is lobbied to send troops. Mozambique's militants are motivated by grievances against the country they perceive did not bring them much benefit, despite the development of reserves major minerals and hydrocarbons. Tanzanians and other foreigners have join forces, sparking a rebellion. The country's historically weak security forces unable to stem the onslaught. If not contained, the rebellion could spread further, threatening stability nationally just as Mozambique fulfills a peace agreement with the opposition the country's primary and heading for national elections in 2024. It can exacerbated instability along the East African coast and provided ISIS with a new front to be exploited. Maputo should receive targeted assistance for security operations suppress rebellion, and avoid the severe external spread that can causing a swamp. The authorities had to mobilize assistance to build trust with the local population and open dialogue with the militants. Government the region must redouble law enforcement efforts to block jihadist involvement transnational.